We are the dinosaurs - Berkner, Laurie; Clanton, Ben, 1988- (New York : Simon & Schuster Books for Young Readers, 2017)
Dinosaurs eat, rest, roar, and march, making the earth flat.
Ages 4-8.
Keywords: Children's songs, English -- United States -- Juvenile literature; American songs; Dinosaurs; Song texts